Shielding Achilles' Heel: Challenges Facing Northern Command in the Maritime Domain - Urbizu, Carlos (2004)
This thesis examines the role U.S. Northern Command (NORTHCOM) is performing in the maritime domain as the new Unitied Command responsible for homeland defense. NORTHCOM does not currently have a permanent maritime component assigned for missions. Instead, it relies on contingency planning for future events and theoretically acts as a coordinating bridge between the Navy and Coast Guard for Maritime Homeland Defense/ Security issues. The primary objective of this research is to answer the question: Can NORTHCOM effectively execute maritime homeland defense and support homeland security without having permanently assigned maritime forces?" Secondly, this thesis seeks to scrutinize the seam in transition from Maritime Homeland Security to Maritime Homeland Defense and explicate potential mission priority, service capability, geographic, and cultural mismatches which could potentially stymie command and control in the transition from a HLS to HLD posture in the event of a seaborne terrorist attack. The original document contains color images.